Xbox Kinect™ represents high intensity exercise for adults with cystic fibrosis - Holmes, H.; Wood, J.; Jenkins, Sue; Winship, P.; Lunt, D.; Bostock, S.; Hill, Kylie (Elsevier B.V., 2013)
Background: Exercise is important for patients with cystic fibrosis (CF). Interactive gaming consoles are a new trend in exercise. This study sought to determine the exercise intensity of training using the Xbox Kinect™. Methods: Participants with CF completed two sessions separated by ≤10 days. The first session involved a cardiopulmonary exercise test (CPET) to measure peak exercise capacity. The second session involved 20 min of exercise using the Xbox Kinect™. Results: Ten participants (median [interquartile range] FEV1 58 [46]%, 29 [6] years, 6 males) completed the study. The average heart rate over the final 10 min of exercise using the Xbox Kinect™, expressed as a percentage of the peak heart rate achieved on the CPET, was 86% (95%confidence interval, 81 to 92%). Conclusions: Training using the Xbox Kinect™ represents high intensity exercise for adults with CF and may be a suitable alternative to conventional exercise modalities.